The experience of hate incidents across racial and ethnic groups during the COVID-19 pandemic - Carolyn A. Fan; KeliAnne K. Hara-Hubbard; Wendy E. Barrington; Wendy E. Barrington; Wendy E. Barrington; Barbara Baquero (Frontiers Media S.A., 2022)
IntroductionRacism is a root cause of ill health for communities of color, and hate incidents are one manifestation of racism. Marginalized racial and ethnic groups, including but not limited to Asian Americans, have been the target of highly publicized violence, hate, and discrimination which has been amplified during the COVID-19 pandemic.ObjectivesThis paper investigates (1) the prevalence of hate incidents across racial and ethnic groups, and (2) the relationship between race and ethnicity and hate incidents during the first year of the COVID-19 pandemic. We also seek to (3) situate study findings within theories of racism.MethodsThis study utilizes national data from the Understanding America Study (UAS) COVID-19 Longitudinal Survey from June 10, 2020 to March 30, 2021 (n = 8,436). Hate incidents in six categories were examined: being treated with less courtesy, receiving poorer service, others acting as if they were not smart, others acting as if they were afraid of them, being threatened or harassed, and experiencing any of the previous categories of hate incidents. Main analyses were conducted via population averaged logistic panel regression.ResultsThe majority of members of all six marginalized racial and ethnic groups reported at least one hate incident during the first year of the COVID-19 pandemic. In addition, all marginalized racial or ethnic groups had statistically significant higher odds of experiencing at least two categories of hate incidents compared to white individuals. Asian, AI/AN, Black, and Multiracial groups had significantly higher odds of experiencing each category of hate incident. All marginalized racial and ethnic groups had significantly higher odds of receiving poorer service and others acting as if they were afraid of them.ConclusionAll marginalized racial and ethnic groups experienced significant levels of hate incidents within the first year of the COVID-19 pandemic. The public health community must continue to research, monitor, treat, and prevent hate incidents as a public health issue while recognizing the social and historical contexts of structural and interpersonal racism in the US.